Immune Response and Safety of Viral Vaccines in Children with Autoimmune Diseases on Immune Modulatory Drug Therapy. (1st December 2020) - Tse, Hiu Nam; Borrow, Ray; Arkwright, Peter D.
ABSTRACT: Introduction : Children with autoimmune diseases often require treatment with systemic immunosuppressives. Efficacy and safety of vaccination, particularly live-attenuated viral vaccines in these patients remain a concern. Areas covered : To evaluate the immunogenicity and safety of viral vaccines in children and young people treated with systemic immunosuppressive drugs for autoimmune diseases. A systemic literature review was performed using Pubmed including English papers in subjects less than 21 years old. Viral vaccines were generally immunogenic and safe in children receiving immunosuppressive drugs, including biologics. Use of low-dose prednisolone or disease-modifying antirheumatic drugs did not significantly impact on vaccine immunogenicity, although there was anecdotal evidence of reduced immunogenicity in patients receiving high-dose prednisolone/methylprednisolone and pulse cyclophosphamide. Patients on biologics mounted adequate seroprotective responses, but antibody titers tended to be lower. Both live-attenuated and inactivated vaccines were well tolerated with no serious adverse events. Autoimmune disease activity was not adversely affected by vaccination. Expert opinion : Current evidence indicates that administration of viral vaccines to children with autoimmune diseases receiving most systemic immunosuppressive drugs is immunogenic and safe. MMR can safely be given to most patients receiving biologics, but patients on high-dose prednisolone and pulse cyclophosphamide should avoid MMR and other live viral vaccines.